Penyuluhan dan Pemberdayaan Masyarakat Menuju Bebas Kecacingan Di Sekolah Dasar Desa Bone Kecamatan Nekamese Kabupaten Kupang - Meliance Bria; Murry Jermias Kale (Cv. Utility Project Solution, 2022)
Worms are a health problem that is still widely found. Worms caused by several intestinal worms transmitted through the soil are called Soil Transmitted Helminths (STH). Elementary school children are an age group that is susceptible to infection with worms. Worm infections can have a serious impact if not treated with deworming medication and a clean and healthy lifestyle of the person. This community service is carried out to be an outreach to improve and empower the community, especially elementary schools, about clean living behavior in dealing with worms. Behaviors such as hand washing habits, nail hygiene, footwear habits, bowel habits and to determine environmental sanitation risk factors such as latrine ownership, availability of clean water, and ownership of trash bins related to stunting in children aged 2-12 years at SDN Bone Bone Village, Nekamese District. The number of students at SDN Bone is 88, in grades 1 to 6. Counseling and community empowerment towards being free from worms at the Elementary School of Bone Village, West Kupang District, Kupang Regency has been carried out well, involving 88 students in grades 1-6. Evaluation of improving understanding of helminthiasis of elementary school students well.